2023
DOI: 10.1111/pcn.13557
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter reserve determines glymphatic system function in young‐onset Alzheimer's disease: Evidenced by DTI‐ALPS and compared with age‐matched controls

Abstract: Background The diffusion tensor imaging analysis along the perivascular space (ALPS)‐index can be used to model the glymphatic system in vivo. Aim This study explores putative mechanisms between prediction of ALPS‐index and cognitive outcomes in young‐onset Alzheimer's disease (YOAD) and age‐matched controls (CTLs) and analyzes whether the link was mediated by the integrity of ALPS‐index‐anchored cerebral gray matter (GM). Methods We enrolled 130 patients with YOAD and 137 CTLs. All participants underwent thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
(85 reference statements)
2
9
0
Order By: Relevance
“…Early studies also indicated that the protective role in education against cognitive decline in MCI is mediated at least partially by changes on cerebral blood flow in right hippocampus ( Zhu et al, 2023 ). This finding was also reported in experiments on young-onset AD to show that the relationship between the ALPS-index and cognitive function was significantly mediated by gray matter reserve ( Chang et al, 2023 ). Similarly, Hisao et al found that a higher ALPS-index suggested a stronger cortical reserve in areas that align with the default mode network, lower ALPS-index and cortical atrophy in specific regions were related to decreased mental manipulation and short-term memory among older individuals ( Hsiao et al, 2023 ).…”
Section: Discussionsupporting
confidence: 78%
“…Early studies also indicated that the protective role in education against cognitive decline in MCI is mediated at least partially by changes on cerebral blood flow in right hippocampus ( Zhu et al, 2023 ). This finding was also reported in experiments on young-onset AD to show that the relationship between the ALPS-index and cognitive function was significantly mediated by gray matter reserve ( Chang et al, 2023 ). Similarly, Hisao et al found that a higher ALPS-index suggested a stronger cortical reserve in areas that align with the default mode network, lower ALPS-index and cortical atrophy in specific regions were related to decreased mental manipulation and short-term memory among older individuals ( Hsiao et al, 2023 ).…”
Section: Discussionsupporting
confidence: 78%
“…Despite the mounting cross‐sectional evidence linking the glymphatic system to cognitive performance in AD, 10 , 15 , 16 , 50 we present the first preliminary evidence that lower ALPS index predicts faster cognitive decline and higher risk of clinical progression in AD adjusting for age, sex, education, and APOE ε4 carrier status. And the effects of white matter pathology or GM atrophy on the ALPS index were not sufficient to shake our main conclusions.…”
Section: Discussionmentioning
confidence: 69%
“…Our study supports the previous finding that brain volume fully mediates the relationship between ALPS index and cognition. 50 Nonetheless, our novel contributions lie in the longitudinal design, the inclusion of Aβ biomarkers, and the use of the multiple mediation model. We found that the glymphatic function, assessed by the ALPS index, may protect against AD‐related cognitive decline mediated not only by brain volume but also by Aβ burden.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental assumption in this method is that the perivascular space is perpendicular to white matter fibers adjacent to the lateral ventricle body. Several studies have used DTI-ALPS to assess the glymphatic system in PwAD and PwPD ( 30 , 46 49 ). All studies found a lower ALPS index in PwND compared to healthy controls (HCs), interpreted as reduced water diffusivity within the perivascular space.…”
Section: Advanced Neuroimaging Methodsmentioning
confidence: 99%
“…In addition to guiding the development and evaluation of new treatments, neuroimaging of the glymphatic system could also contribute to personalized treatment strategies for PwND. Given the clinical heterogeneity and the variability in glymphatic function between PwND, treatments that enhance glymphatic function may be equally effective only in some patients ( 30 , 31 ). Here, neuroimaging can provide information on an individual’s glymphatic function, allowing for the personalization of treatment strategies based on this information.…”
Section: Overview Of the Glymphatic Systemmentioning
confidence: 99%